The Use of Water Hyacinth Leaves Supplementation in Ruminant Feed on Methane, Protozoa, VFAs, and Fatty Acids Ruminal Fluid in Vitro - Sondakh, Erwin Hubert Barton; Kalele, Jerry; Tuwaidan, Nancy (Faculty of Animal Science, Jenderal Soedirman University in associate with the Animal Scientist Society of Indonesia (ISPI) and the Indonesian Association of Nutrition and Feed Science (AINI), 2024)
This study aims to determine the effect of water hyacinth leaves supplementation in ruminant feed parameters of fermentation, and fatty acids ruminal fluid in vitro. The experiment consists of six treatments, R0: no water hyacinth + 30% concentrate; R1: 1% water hyacinth leaves + 29% concentrate; R2: 2% water hyacinth leaves + 28%; R3: 3% water hyacinth leaves + 27% water hyacinth leaves; R4: 4% water hyacinth leaves + 26% concentrate; R5: 5% water hyacinth leaves + 25% concentrate. The fermentation was conducted at 39oC for 72 hours using gas production technique. The results indicated that giving of 4% water hyacinth leaves and 26% concentrate of MCFA could reduce the number of protozoa and methane production (P<0.05) and increase propionate acid. It can be concluded that use of 4% water hyacinth leaves and 26% concentrate could reduce methane gas production and quantity of protozoa and also could increase propionate acid in rumen fermentation in vitro.